Analysis of Income Tax Tariff Free Policy in Improving Compliance of MSME WPOPs in Manado City - Poluakan, Angely Agnes; Kalangi, Lintje; Korompis, Claudia (Formosa Journal of Applied Sciences, 2025)
This study aims to examine the implementation of the income tax rate exemption policy for individual taxpayers engaged in the MSME sector with gross income not exceeding Rp500,000,000, with the aim of increasing reporting compliance in the jurisdiction of KPP Pratama Manado. A qualitative approach is used in this research using descriptive qualitative methodology. The results of the study explain that the PPh tariff-free policy in PP No. 55 of 2022 socialized by KPP Pratama Manado really has an impact on the compliance ratio of annual tax return reporting for MSME WPOPs in Manado City. However, the impact has not been maximized enough, so that the growth of registered and reporting MSME WPOPs has not experienced a large change.